2016
DOI: 10.1161/circimaging.115.003810
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Volumes and Systolic Function by Cardiac Magnetic Resonance and the Impact of Sex, Age, and Obesity in a Longitudinally Followed Cohort Free of Pulmonary and Cardiovascular Disease

Abstract: R ight ventricular (RV) size and systolic function have diagnostic and prognostic value in multiple cardiovascular and pulmonary disorders. [1][2][3][4] However, because of its substernal position and crescentic shape, the right ventricle has been difficult to characterize using conventional 2-dimensional echocardiography. Cardiac magnetic resonance (CMR) provides highly reproducible measures of RV volumes and systolic function. 5,6 See Editorial by Fent and PleinSee Clinical Perspective CMR is considered the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 21 publications
5
42
0
1
Order By: Relevance
“…Normal reference values for ventricular sizes and function by MRI is fundamental for the diagnosis of heart disease. Several studies from different centers (primarily in the USA and Europe) have provided normal reference values for ventricular sizes and function using MRI for healthy subjects without cardiovascular disease or patients with cardiovascular disease of European descent . Age‐ and sex‐based reference values of ventricular sizes and function in a broad age range of the adult population of mainland China are lacking.…”
mentioning
confidence: 99%
“…Normal reference values for ventricular sizes and function by MRI is fundamental for the diagnosis of heart disease. Several studies from different centers (primarily in the USA and Europe) have provided normal reference values for ventricular sizes and function using MRI for healthy subjects without cardiovascular disease or patients with cardiovascular disease of European descent . Age‐ and sex‐based reference values of ventricular sizes and function in a broad age range of the adult population of mainland China are lacking.…”
mentioning
confidence: 99%
“…Although the normal RV values reported by the authors represent the most robust currently available using SSFP CMR for middle aged to elderly subjects, they do not apply to younger patients. Indeed, quoted reference ranges for younger subjects in other studies fall outside the 95% confidence intervals reported by Foppa et al 11 As such, the use of alterative reference ranges 12,13 for RV volumes and systolic function in younger adult patients is advised.…”
Section: Fent and Pleinmentioning
confidence: 85%
“…The authors reported increased RVEF with advancing age, increased RV end-diastolic volume but lower RVEF in men versus women, lower RVEF in black versus white individuals as well as higher right ventricular enddiastolic volume and lower RVEF in obese individuals. 8,9 Several other studies 7,10 have provided normal reference ranges for RV volumes and systolic function using contemporaneous SSFP acquisition, but these are on a much smaller scale than the study by Foppa et al 11 in this issue of Circulation: Cardiovascular Imaging.…”
Section: See Article By Foppa Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The right ventricular trabeculation are pronounced, but limited data is available regarding quantitative measurement of these structures in a normal population [9,14,15] or in pathological conditions [6,16]. Large population based studies provide normal RV values excluding small intracavitary structures from RV mass [17][18][19].…”
Section: Introductionmentioning
confidence: 99%